Abnormal pressures while drilling : origins, prediction, detection, evaluation - Mouchet, Jean-Paul; Mitchell, Alan (Editions Technip, 1989)
Annotation This practical handbook brings together a wide range of bibliographic information on abnormal pressures and adds the practical experience of the authors and various experts within Elf-Aquitaine. Primarily destined for day to day use by subsurface geologists and drilling engineers wherever they are confronted with the problems of overpressure, it describes the various origins of pressure anomalies, and details the methods available for their prediction, detection and evaluation. It will also be useful to petroleum geologists, petroleum engineers and reservoir engineers as a reference manual.
Keywords: Oil well drilling.; Gas well drilling.; Reservoir oil pressure.; elektronické knihy; electronic books